Leading the way in pediatric sexual health screenings: evaluating pediatric emergency department workflows for the integration of STI screening tools - Schubel, Laura; Busog, Deanna-Nicole; Tabaie, Azade; Lemke, Monika; Foltz, Danielle; Badolato, Gia; Kaushal, Natasha Ajay; Goyal, Monika K.; Miller, Kristen (Frontiers in Health Services, 2025)
IntroductionEmergency department (ED) encounters offer strategic opportunities for sexually transmitted infection (STI) screening, prevention, and treatment for adolescents at risk for STIs who may not otherwise have access to routine screening. This study determined optimal ED implementation of the Teen Health Screen (THS), a validated, tablet-based, patient-reported, sexual risk assessment, and evaluated its implementation feasibility under variable workflows and high-stress tasks.MethodsWorkflow analysis included semi-structured interviews with patients, caregivers, and clinical staff members and clinical observations to understand patient and clinical workflow. The study was conducted in two urban pediatric EDs over six weeks. Participants included patients, parents/caregivers, registration staff, nurses, social workers, child life specialists, providers, and health IT experts.ResultsThe primary study outcome was development of a general model of ED workflow and patient-clinician engagement, focusing on patient flow, clinical tasks, people, and technologies involved. Workflow analyses identified key opportunities for THS deployment during the nurse assessment process, which aligns with other existing screening activities and offers privacy. This approach addresses potential barriers to integration such as privacy concerns, language and literacy barriers, the sensitivity of discussing sexual history, comfort with technology, tablet accessibility and security, and internet availability.DiscussionWorkflow analysis provided valuable insights to the perceptions, thoughts, and practicality of implementing the THS in the ED. Interviews revealed general acceptance of the new process but highlighted logistical challenges, particularly with staffing and patient surge. Implementing the THS in ED settings appears feasible, with important opportunities identified for integration to improve patient safety, including staffing and workflow optimization.